Superior Intrinsic Mitochondrial Respiration in Women Than in Men - Cardinale, Daniele A.; Larsen, Filip J.; Schiffer, Tomas A.; Morales-Alamo, David; Ekblom, Björn; Calbet, Jose A. L.; Holmberg, Hans-Christer; Boushel, Robert (Frontiers in Physiology, 2018)
Sexual dimorphism is apparent in humans, however to date no studies have investigated mitochondrial function focusing on intrinsic mitochondrial respiration (i.e. mitochondrial respiration for a given amount of mitochondrial protein) and mitochondrial oxygen affinity (p50mito) in relation to biological sex in human. A skeletal muscle biopsy was donated by nine active women, and ten men matched for maximal oxygen consumption (VO2max) and by nine endurance trained men. Intrinsic mitochondrial respiration, assessed in isolated mitochondria, was higher in women compared to men when activating complex I (CIP) and complex I+II (CI+IIP) (p<0.05), and was similar to trained men (CIP, p=0.053; CI+IIP, p=0.066). Proton leak and p50mito were higher in women compared to men independent of VO2max. In conclusion, significant novel differences in mitochondrial oxidative function, intrinsic mitochondrial respiration and p50mito exist between women and men. These findings may represent a adaptation in the oxygen cascade in women to optimize muscle oxygen uptake to compensate for a lower oxygen delivery during exercise.